A Review of Research Connecting Digital Storytelling, Photovoice, and Civic Engagement. (December 2018) - Greene, Stuart; Burke, Kevin J.; McKenna, Maria K.
The purpose of this review is to expand understanding of the ways culturally, ethnically, and racially diverse youth have begun to reimagine urban and rural spaces using digital storytelling and photovoice, two methods that often fall under the broad field of youth participatory action research. To explain the conditions under which these methods favor movement toward socially just ideas and actions, we also build on and extend research in critical youth empowerment to call attention to the relational nature of the kind of work that positions youth as coresearchers and democratically engaged citizens. Of importance are the availability of safe, nurturing spaces that foster youth engagement, the quality of relationships between youth and adults, and the extent to which decisions and actions remain in the hands of youth. Finally, this review considers the implications for further research and what it could mean to reimagine schools and communities as spaces where youth have a voice as civically engaged citizens.